Hydroulic stand for testing automatic seats model development - Virchenko, Viktor; Shapoval Мykola; Skoryk, Maxym; Ladur, Vladyslav (Academic journal Industrial Machine Building Civil Engineering, 2018)
A new design scheme for testing the car seats with hydraulic drive has been proposed, a mathematical model of stand work process has been developed, the movement of mass center in the car seat has been theoretically proved. It is determined at the expense of what factors it is necessary to develop special stands necessary for an adequate various seats check or seat configurations, which simulate long-term seats use during a short time period. The special stands car seats of different configurations work analysis simulation close to the real operation conditions on cars is carried out. The basic parameters and operating modes that characterize working processes in the conditions of operation are established. The mathematical dependence, which characterizes the work process of the stand for testing the car seat with a hydraulic drive, is obtained. The movement of car seat masses center depending on the influence factors is determined.